THE EFFECT OF FINANCIAL DISTRESS, FINANCIAL RATIO, AND GOOD CORPORATE GOVERNANCE ON EARNINGS MANAGEMENT - Putri, Rini Oktaviani; Arum, Enggar Diah Puspa; Hernando, Riski (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2024)
The goal of earnings management, an agency-related issue, is to choose accounting rules that would enhance profits in line with the goals of the business while creating financial statements. The corporation takes this measure when it can't turn a profit that it wants to. This study aims to examine the variables that affect the incidence of earnings management. The study focused in the property, real estate, and building construction industries between 2020-2022. Purposive sampling was used in the research sample, which consisted of 54 companies. Secondary data using various linear regression data analysis approaches were used in this study. According to research findings based on multiple linear regression tests, financial strain partially has no effect on earnings management. Financial ratio proxied by profitability partially has a negative effect on earnings management, but liquidity and leverage partially have no effect. And than, earnings management is not entirely impacted by good corporate governance, which is audit committee, managerial ownership, and independent board of commissioners. Earnings management is, however, simultaneously impacted by financial distress, financial ratios, and good corporate governance.Keywords: Financial Distress, Financial Ratio, Good Corporate Governance, Earnings Management.